Proteomic analysis of T. qataranse exposed to lead (Pb) stress reveal new proteins with potential roles in Pb tolerance and detoxification mechanism - Usman, Kamal; Souchelnytskyi, Serhiy; Al-Ghouti, Mohammad A.; Zouari, Nabil; Abu-Dieyeh, Mohammed H. (Frontiers in Plant Science, 2022)
Lead (Pb) is the second most toxic metal on earth. Phytoremediation is an emerging technology to rid the environment of toxic metals, including Pb. Current work in this area is invested in elucidating mechanisms that underpin toxic metals tolerance and detoxification mechanisms. The present study aims to gain insight into the mechanisms of Pb tolerance in T. qataranse by comparative proteomics. MALDI-TOF/MS and in silico proteome analysis showed differential protein expression between treated (50 mg/kg Pb) and untreated (0 mg/kg Pb) T. qataranse. A total of eighty-six (86) differentially expressed proteins, most of which function in ion and protein binding, antioxidant activity, transport, and abiotic response stress, were identified. In addition, essential stress regulating metabolic pathways, including glutathione metabolism, cellular response to stress, and regulation of HSF1-mediated heat shock response, were also enriched. Also, at 52 and 49 kDa MW band areas, up to six hypothetical proteins with unknown functions were identified. Of these, protein AXX17_AT2G26660 is highly rich in glycine amino acid residues (up to 76%), suggesting that it is a probable Glycine Rich Proteins (GRPs) member. Although GRPs are known to be involved in plant defense against abiotic stress, including salinity and drought, there is no report on their role on Pb tolerance and or detoxification in plants. Further enrichment analysis in the current study reveals that the hypothetical proteins do not interact with known proteins and are not part of any enriched pathway. However, additional research is needed to functionally validate the role of the identified proteins in Pb detoxification mechanism.